Refining Single-Atom Catalytic Kinetics for Tumor Homologous-Targeted Catalytic Therapy - Hengke Liu; Shan Lei; Hongyu Li; Jiayingzi Wu; Ting He; Jing Lin; Peng Huang (Nano-Micro Letters)
Highlights Developed a dual-enzyme cascade system integrating iridium single-atom nanozymes with glucose oxidase, optimizing hydrogen peroxide production, acidity, and temperature within the tumor microenvironment to markedly improve catalytic therapy efficacy. Functionalized the cascade reaction system with cancer cell membranes to achieve homologous targeting and high biocompatibility, ensuring accurate accumulation at tumor sites while minimizing off-target effects.